VERIFICATION AND OPTIMISATION OF PRESELECTED EXPOSURE PARAMETERS IN SCREENING MAMMOGRAPHY: A CENTRAL COMPOSITE DESIGN METHODOLOGY. Issue 3 (16th January 2020) - Acho, Sussan N; Stofile, Caroline; Moller, Mia; Morphis, Michaella
Abstract: In screening mammography, the automatic exposure control (AEC) device selects the optimum exposure parameters for each patient exposure. In practice, this device is calibrated to deliver an optimum figure of merit (FOM) for each set of exposure parameters. This study utilises the central composite design methodology to verify the operating level of the AEC performance for polymethyl methacrylate (PMMA) thicknesses of 4 and 5 cm. Quadratic surface plots reveal that the exposure parameters of the default AEC mode are optimised for the 4-cm thickness of the PMMA. However, the exposure parameters of the 5-cm thickness of PMMA need fine-tuning to obtain a maximum value for the FOM.